Malaria parasitemia among blood donors in Uganda. Issue 5 (13th April 2020) - Murphy, Kristin J.; Conroy, Andrea L.; Ddungu, Henry; Shrestha, Ruchee; Kyeyune‐Byabazaire, Dorothy; Petersen, Molly R.; Musisi, Ezra; Patel, Eshan U.; Kasirye, Ronnie; Bloch, Evan M.; Lubega, Irene; John, Chandy C.; et al.
Abstract : BACKGROUND: Malaria remains a leading transfusion associated infectious risk in endemic areas. However, the prevalence of malaria parasitemia has not been well characterized in blood donor populations. This study sought to determine the prevalence of Plasmodium in red blood cell (RBC) and whole blood (WB) units after the rainy season in Uganda. METHODS AND MATERIALS: Between May and July 2018, blood was collected from the sample diversion pouch of 1000 WB donors in Kampala and Jinja, Uganda. The RBC pellet from ethylenediamine tetraacetic acid (EDTA) anticoagulated blood was stored at −80°C until testing. DNA was extracted and nested PCR was used to screen samples at the genus level for Plasmodium, with positive samples further tested for species identification. RESULTS: Malaria parasitemia among asymptomatic, eligible blood donors in two regions of Uganda was 15.4%; 87.7% (135/154) of infections were with P. falciparum, while P. malariae and P. ovale were also detected. There were 4.3% of blood donors who had mixed infection with multiple species. Older donors (>30 years vs. 17‐19 years; aPR = 0.31 [95% CI = 0.17‐0.58]), females (aPR = 0.60 [95% CI = 0.42‐0.87]), repeat donors (aPR = 0.44 [95% CI = 0.27‐0.72]) and those donating near the capital city of Kampala versus rural Jinja region (aPR = 0.49 [95% CI = 0.34‐0.69]) had a lower prevalence of malaria parasitemia. CONCLUSIONS: A high proportion of asymptomatic blood donors residing in a malaria endemic region demonstrate evidence of parasitemia at time of donation. Further research is needed to quantify the risk and associated burden of transfusion‐transmitted malaria (TTM) in order to inform strategies to prevent TTM.